2017
DOI: 10.1155/2017/2320519
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Supplements Improve Cultured Megakaryocyte Polyploidization by Modulating Multiple Cell Cycle Regulators

Abstract: Platelets (PLTs) are produced by megakaryocytes (MKs) that completed differentiation and endomitosis. Endomitosis is an important process in which the cell replicates its DNA without cytokinesis and develops highly polyploid MK. In this study, to gain a better PLTs production, four small molecules (Rho-Rock inhibitor (RRI), nicotinamide (NIC), Src inhibitor (SI), and Aurora B inhibitor (ABI)) and their combinations were surveyed as MK culture supplements for promoting polyploidization. Three leukemia cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
1
10
0
2
Order By: Relevance
“…Therefore, we confirmed that RHOB expression inversely correlated with miR-1915-3p expression. A few previous reports 24 , 25 and our study 26 demonstrated that SCR and ROCK , downstream effectors of RHOB , acted as negative regulators of MK differentiation. Accordingly, we deduced that miR-1915-3p carried by PMPs was transported to target cells and suppressed RHOB expression in target cells, thereby inducing megakaryocytic differentiation and maturation (Supplementary Fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Therefore, we confirmed that RHOB expression inversely correlated with miR-1915-3p expression. A few previous reports 24 , 25 and our study 26 demonstrated that SCR and ROCK , downstream effectors of RHOB , acted as negative regulators of MK differentiation. Accordingly, we deduced that miR-1915-3p carried by PMPs was transported to target cells and suppressed RHOB expression in target cells, thereby inducing megakaryocytic differentiation and maturation (Supplementary Fig.…”
Section: Resultssupporting
confidence: 63%
“…The Rho/ROCK pathway is well acknowledged as a negative regulator of MK endomitosis and proplatelet formation 24,37 . RHOB activated SCR and ROCK 24,25 , and inhibitors of SCR and ROCK promoted MK differentiation and maturation 26 . Accordingly, PMPs contained high levels of miR-1915-3p and might induce MK differentiation of recipient cells by inhibiting the Rho/ROCK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…AURKB is actively involved in mitosis, chromosomal alignment and segregation, formation of the cleavage furrow, and control of checkpoints, and therefore prevents the occurrence of aneuploidy [83,85,86]. In fact, inhibition of AURKB has been found to lead to polyploidy in vitro in both cancer and non-cancer cells [83,84,86,96]. AURKC is the least-studied member of the family.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the mRNA level of p21 and GAPDH was quantified using SYBR Premix ExTaq (TaKaRa, Tokyo, Japan) with the 2 −ΔΔCt method according to the manufacturer's instructions. The primer sequences are shown in Table 33–35 …”
Section: Methodsmentioning
confidence: 99%